The girl with the dragon tattoo eaudiobook - Larsson, Stieg (Millennium,, 2008)
ONE OF TIME MAGAZINE 'S 100 BEST MYSTERY AND THRILLER BOOKS OF ALL TIME • #1 NATIONAL BESTSELLER • The thrilling first book in the Girl with the Dragon Tattoo series featuring Lisbeth Salander: “Combine the chilly Swedish backdrop and moody psychodrama of a Bergman movie with the grisly pyrotechnics of a serial-killer thriller, then add an angry punk heroine and a down-on-his-luck investigative journalist, and you have the ingredients of Stieg Larsson’s first novel” ( The New York Times ). • Also known as the Millennium series Harriet Vanger, a scion of one of Sweden's wealthiest families disappeared over forty years ago. All these years later, her aged uncle continues to seek the truth. He hires Mikael Blomkvist, a crusading journalist recently trapped by a libel conviction, to investigate. He is aided by the pierced and tattooed punk prodigy Lisbeth Salander. Together they tap into a vein of unfathomable iniquity and astonishing corruption. Look for the latest book in the Girl with the Dragon Tattoo series, The Girl in the Eagle's Talons !